FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KECEMASAN MAHASISWA SAAT MENGIKUTI PEMBELAJARAN HYBRID - Nanda Nabila Al Jannah; Liana Septy (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2023)
The Covid-19 pandemic has an impact on all aspects of people's lives, including in the field of education, which has caused the government to issue policies to carry out online learning activities. Over time, the government has again reviewed the level of spread of Covid-19 in Indonesia and issued a new normal policy so that learning activities that were originally carried out fully online have now turned into hybrid learning. Hybrid learning is a combination of online and offline learning systems. The impact of this hybrid learning system is the anxiety experienced by students. Therefore, this article describes the factors that cause anxiety through interview data and filling out questionnaires to several students of Raden Fatah Islamic State University.